2003
DOI: 10.1046/j.1365-2923.2003.01412.x
|View full text |Cite
|
Sign up to set email alerts
|

Early clinical exposure to people who are dying: learning to care at the end of life

Abstract: The way in which many of these students approach end-of-life care has been altered through a transformative educational experience that encouraged them to draw on their own experiences and skills. Their learning was facilitated by the writing of accounts and the discussion that each group held with teaching staff at the conclusion of the programme.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
89
0
5

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(101 citation statements)
references
References 13 publications
7
89
0
5
Order By: Relevance
“…19,31,32 Recently, portfolio assessment was introduced as a method to assess competences including professional and personal skills. 46,47 Combining the above mentioned assessment programmes with portfolio assessment is also a strategy that merits further exploration. E.g., the results of the tests could be collected in a portfolio which should be discussed on several occasions in the course of a clerkship.…”
Section: Conclusion For Feasibility and Reliability Aspects Of In-trmentioning
confidence: 99%
See 1 more Smart Citation
“…19,31,32 Recently, portfolio assessment was introduced as a method to assess competences including professional and personal skills. 46,47 Combining the above mentioned assessment programmes with portfolio assessment is also a strategy that merits further exploration. E.g., the results of the tests could be collected in a portfolio which should be discussed on several occasions in the course of a clerkship.…”
Section: Conclusion For Feasibility and Reliability Aspects Of In-trmentioning
confidence: 99%
“…Finally, including global performance ratings and portfolio assessments into these assessment programmes offers interesting possibilities for enhancing reliability and broadening the range of competences that can be assessed. 46,47 Effects of an in-training programme on the learning environment In all three clerkships studied, supervision (particularly observation) was sparse for all competences, feedback was mainly provided by residents and assessment mostly targeted patient-related competences. For all variables, the variation between students exceeded that between disciplines.…”
Section: Conclusion For Feasibility and Reliability Aspects Of In-trmentioning
confidence: 99%
“…There has been growing interest in palliative care related issues in undergraduate medical training programmes which has been reflected in an increase in the number of hours taught (Hillier & Wee 2001, Field & Wee 2002, MacLeod et al 2003, Kelly & Nisker 2010. However, there is little known about the effectiveness of end-of-life care classroom-based teaching and, even when included, Kelly & Nisker (2010) report that the emotional aspect of caring for the dying is often not addressed.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, Clouder (2005) suggests that student health professionals are not exposed to caring discourse, including emotional and affective aspects of professional learning, at undergraduate level. Some research advocates learning through experience (Hillier & Wee 2001, MacLeod et al 2003, which has been reflected in the types of teaching methods now used in medical schools, that often include meeting a dying patient or hospice placements (Field & Wee 2002). It is also suggested that experiential learning can be enhanced through positive role-modelling (Peterson et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…1 In 2000, palliative care was directly addressed in 87% of U.S. medical schools, and students had direct exposure to a hospice patient, 1 an intervention that can greatly enhance students' and spiritual awareness and enable them to care more effectively for people who are dying. 2 Nonetheless, an international survey of undergraduate medical education in palliative medicine revealed that as of 2000, rotations in undergraduate palliative medicine education were lacking in Canadian, U.S., and Western European medical schools, and that the majority of medical schools had only one faculty member in palliative medicine. 3 Furthermore, postgraduate specialty training programs in the United States suffer from a lack of comprehensive EOL training requirements across programs.…”
mentioning
confidence: 99%